Characterization of non-structural carbohydrate of two cultivars of Dioscorea hispida Dennst - Muhammad Zulkarnain Mustafa (2019)
Dioscorea hispida Dennst (D. hispida) or commonly known as ubi gadong in Malaysia is one of carbohydrate source which is act as food source among local people. D. hispida is abundantly found in the east coast of peninsular Malaysia. There are two varieties of D. hispida can be found in Malaysia which is yellow D. hispida and white D. hispida. D. hispida is unpopular food source due to its toxic content which makes it a good source alternative for bioproduct development. Non-structural carbohydrate (NSC) which refer to starch and sugar can be used in fermentation process in bioethanol production. As the first step of application, systematic information of NSC is importance for formulation purpose by industry. The aims of this research project were focus on characterize starch and sugar on tuber part of two varieties of D. hispida cultivar. Enzymatic hydrolysis methods shows that yellow D. hispida contain higher starch percentage which is 25.58% compared to white D. hispida that is only 8.66%. Sugar concentration analysis using refractometer on D. hispida sap show that both cultivar studied have low sugar concentration, which yellow D. hispida was slightly higher which is 6.2% whereas white D. hispida was only 6.0%. The starch were further characterize by using Scanning Electron Microscope – Energy Dispersive X-ray (SEM-EDX) and X-ray Diffraction (XRD). Apart from NSC characterization, the physical analysis was also done which is colour measurement by colorimeter.